Morphological characteristics and morphometrics of Stingless Bees (Hymenoptera: Meliponini) in Yogyakarta, Indonesia - Manap Trianto; Hari Purwanto (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Trianto M, Purwanto H. 2020. Morphological characteristics and morphometrics of Stingless Bees (Hymenoptera: Meliponini) in Yogyakarta, Indonesia. Biodiversitas 21: 2619-2628. Stingless bees (Apidae: Meliponinae) are eusocial insects living together in a colony with a highly organized system. Also, these bees have morphological and morphometric characters that vary among species, islands, and environmental types. This paper described morphological characteristics and morphometric study of stingless bees from the Special Region of Yogyakarta Province, Indonesia. There were seven species of stingless bees found in the Special Region of Yogyakarta, namely Tetragonula laeviceps, T. iridipennis, T. biroi, T. sapiens, T. sarawakensis, Lepidotrigona terminata, and Heterotrigona itama. The morphometry of the stingless bees obtained in this study has varying sizes compared to the same species that have been reported elsewhere. In this study, we described the morphological and morphometric characteristics of the seven species of stingless bees in the Special Region of Yogyakarta Province, Indonesia, and presented the PCA analysis to figure out the grouping characters in order to determine its diagnostic characters.